Positive electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

JP2026167151APending Publication Date: 2026-10-14SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025060572
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0010】 本発明の一態様によれば、非水電解質二次電池の性能を維持しつつ、非水電解質二次電池の安全性を高めることが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167151000001_ABST
    Figure 2026167151000001_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery that can enhance the safety of a non-aqueous electrolyte secondary battery while maintaining its performance. [Solution] A positive electrode for a non-aqueous electrolyte secondary battery is provided, comprising at least a positive electrode current collector, a positive electrode active material layer, and an intermediate layer disposed between the positive electrode current collector and the positive electrode active material layer, wherein the intermediate layer comprises first particles which are lithium iron phosphate particles and an insulating material, the insulating material comprises second particles and a binder, and the content of the first particles in the intermediate layer, the content of the second particles in the intermediate layer, the content of the binder in the intermediate layer, the total content of the first and second particles, the particle diameter of the first particles, the particle diameter of the second particles, and the (D50 determined by laser diffraction / scattering method) / (thickness measured by scanning electron microscope) of the second particles are all within a predetermined range.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a positive electrode for a non-aqueous electrolyte secondary battery, and to a non-aqueous electrolyte secondary battery. [Background technology]

[0002] Non-aqueous electrolyte rechargeable batteries, including lithium-ion batteries, are widely used as power sources for smartphones and laptop computers, and recently they have also been used in large batteries for automotive applications. However, while lithium-ion batteries have the advantage of high energy density, they also have the problem of requiring sufficient safety measures because they use non-aqueous electrolytes. In recent years, as batteries have become larger, ensuring safety has become even more important.

[0003] For example, when operating a vehicle equipped with lithium-ion secondary batteries, there is a possibility that a sharp foreign object, such as a nail, may fly in and pierce the lithium-ion secondary battery while it is in use. If a sharp foreign object such as a nail pierces the battery, it may cause a short circuit between the positive and negative electrodes. In particular, if the positive electrode current collector and the positive electrode active material layer deform, causing the positive electrode active material layer to peel off from the positive electrode current collector and the exposed positive electrode current collector to come into contact with the negative electrode, a very large amount of heat may be generated.

[0004] Therefore, as a countermeasure against foreign objects becoming embedded in lithium-ion secondary batteries, it is conceivable to provide an intermediate layer that can suppress the exposure of the positive electrode current collector even if the positive electrode active material layer peels off from the positive electrode current collector due to deformation of the positive electrode active material layer. As an example of such an intermediate layer, as described in Patent Document 1, an intermediate layer provided between the positive electrode current collector and the positive electrode active material layer and containing highly safe lithium iron phosphate (LFP) particles can be cited. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Special Publication No. 2023-517214 [Overview of the Initiative] [Problems that the invention aims to solve]

[0006] While the safety of non-aqueous electrolyte secondary batteries can be improved by using the intermediate layer disclosed in Patent Document 1 as the positive electrode, the increasing size of batteries in recent years has necessitated further improvements in safety.

[0007] The inventors diligently studied the intermediate layer and found that by incorporating not only the first particles but also second particles having a specific aspect ratio (major axis / minor axis) and a binder into the intermediate layer, and by appropriately controlling the content and particle size of each component, they succeeded in dramatically improving the safety of the non-aqueous electrolyte secondary battery while maintaining its performance.

[0008] The present invention aims to solve the above-mentioned problems, and its objective is to provide a positive electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery that can improve the safety of a non-aqueous electrolyte secondary battery while maintaining the performance of the non-aqueous electrolyte secondary battery. [Means for solving the problem]

[0009] According to one aspect of the present invention, there is provided a positive electrode for a non-aqueous electrolyte secondary battery, comprising at least a positive electrode current collector, a positive electrode active material layer, and an intermediate layer disposed between the positive electrode current collector and the positive electrode active material layer, wherein the intermediate layer includes first particles that are lithium iron phosphate particles and an insulating material, the insulating material includes second particles and a binder, and when the total mass of the intermediate layer is taken as 100% by mass, the content of the first particles in the intermediate layer is 70% by mass or more and 90% by mass or less, the content of the second particles in the intermediate layer is 5.0% by mass or more and 20% by mass or less, the content of the binder in the intermediate layer is 3.0% by mass or more and 10% by mass or less, the total content of the first particles and the second particles is 80% by mass or more and 95% by mass or less, the particle diameter of the first particles is 0.1 μm or more and 3.0 μm or less, the particle diameter of the second particles is 2.9 μm or more and 13.0 μm or less, and the (D50 determined by a laser diffraction / scattering method) / (thickness measured with a scanning electron microscope) of the second particles is 9.0 or more and 40.0 or less. Effects of the Invention

[0010] According to one embodiment of the present invention, it is possible to enhance the safety of a non-aqueous electrolyte secondary battery while maintaining the performance of the non-aqueous electrolyte secondary battery. Brief Description of the Drawings

[0011] [Figure 1] It is a diagram schematically showing the overall configuration of a non-aqueous electrolyte secondary battery according to an embodiment of the present invention. [Figure 2] It is a diagram schematically showing an enlarged part of the intermediate layer. Modes for Carrying Out the Invention

[0012] 1. Overview of Embodiment First, an outline of a representative embodiment of the invention disclosed in the present application will be described. In the following description, as an example, reference numerals on the drawings corresponding to the constituent elements of the invention are described with parentheses attached thereto.

[0013] [1] Positive electrode current collector (21), Positive electrode active material layer (22), A positive electrode for a non-aqueous electrolyte secondary battery, comprising at least an intermediate layer (21a) disposed between the positive electrode current collector and the positive electrode active material layer, The intermediate layer comprises a first particle (21b) which is lithium iron phosphate particles and an insulating material. The insulating material comprises a second particle (21c) and a binder (21d), When the total mass of the intermediate layer is 100% by mass, the content of the first particles in the intermediate layer is 70% by mass or more and 90% by mass or less, the content of the second particles in the intermediate layer is 5.0% by mass or more and 20% by mass or less, and the content of the binder in the intermediate layer is 3.0% by mass or more and 10% by mass or less. The total content of the first particles and the second particles is 80% by mass or more and 95% by mass or less. The particle size of the first particle is 0.1 μm or more and 3.0 μm or less. A positive electrode (20) for a non-aqueous electrolyte secondary battery, wherein the particle diameter of the second particle is 2.9 μm or more and 13.0 μm or less, and the (D50 determined by laser diffraction / scattering method) / (thickness measured by scanning electron microscope) of the second particle is 9.0 or more and 40.0 or less. [2] The positive electrode for a non-aqueous electrolyte secondary battery according to [1], wherein the thickness of the intermediate layer is 0.5 μm or more and 5.0 μm or less.

[0014] [3] A positive electrode for a non-aqueous electrolyte secondary battery according to [1] or [2], wherein the volume resistivity of the first particle when pressurized at 60 MPa is 1.0 Ωcm or more and 5 × 10 Ωcm or less.

[0015] [4] The positive electrode for a non-aqueous electrolyte secondary battery according to any one of [1] to [3], wherein the intermediate layer is composed of at least the first particles and the insulating material.

[0016] [5] The binder comprises a copolymer containing units derived from a (meth)acrylonitrile monomer and units derived from a (meth)acrylic acid monomer, wherein in the copolymer, when the total mass of the copolymer is 100% by mass, the units derived from the (meth)acrylonitrile monomer are 90% by mass or more and 99% by mass or less, and the units derived from the (meth)acrylic acid monomer are 1% by mass or more and 10% by mass or less, as described in any one of [1] to [4].

[0017] [6] The specific surface area (BET) of the first particle, calculated by the adsorption isotherm obtained by adsorbing nitrogen onto the first particle, is 1.0 m². 2 / g or more 20m 2 It is less than / g The specific surface area (BET) of the second particle, calculated by the adsorption isotherm obtained by adsorbing nitrogen onto the second particle, is 0.5 m². 2 / g or more 50m 2 A positive electrode for a non-aqueous electrolyte secondary battery, specified in any one of [1] to [5], which is less than or equal to / g.

[0018] [7] The positive electrode for a non-aqueous electrolyte secondary battery according to any one of [1] to [6], wherein the second particle is one or more selected from the group consisting of boehmite, mica, and boron nitride.

[0019] [8] The second particle comprises composite particles in which the surface and interior of metal hydroxide particles are modified with a flame retardant. The positive electrode for a non-aqueous electrolyte secondary battery according to any one of [1] to [6], wherein the metal hydroxide is one or more selected from the group consisting of aluminum hydroxide, pseudoboehmite, and boehmite.

[0020] [9] The positive electrode for a non-aqueous electrolyte secondary battery according to [8], wherein the flame retardant comprises one or more selected from the group consisting of phosphoric acid, phosphoric acid esters, phosphonic acid, and phosphinic acid.

[0021]

[10] The positive electrode for a non-aqueous electrolyte secondary battery according to [9], wherein, when the total mass of the composite particles is 100% by mass, the content of aluminum element measured by inductively coupled plasma atomic emission spectrometer (ICP-AES) is 5% by mass or more and 30% by mass or less, and the content of phosphorus element is 5% by mass or more and 30% by mass or less.

[0022]

[11] A non-aqueous electrolyte secondary battery (10) comprising a positive electrode for a non-aqueous electrolyte secondary battery described in any one of [1] to

[10] .

[0023] 2. Specific Examples of Embodiments Hereinafter, specific examples of embodiments of the present invention will be described with reference to the drawings. In the following description, common components in each embodiment will be denoted by the same reference numerals, and repeated explanations will be omitted. Also, the drawings are schematic. That is, the dimensions of each element and the ratios between each element in the drawings may differ from actual values.

[0024] <Nonaqueous electrolyte secondary battery> The configuration of the non-aqueous electrolyte secondary battery 10 according to this embodiment will be described based on Figures 1 and 2. Figure 1 is a schematic diagram showing the overall configuration of the non-aqueous electrolyte secondary battery 10. Figure 2 is a schematic diagram showing an enlarged portion of the intermediate layer 21a. The non-aqueous electrolyte secondary battery 10 is, for example, a lithium-ion secondary battery. The non-aqueous electrolyte secondary battery 10 includes a positive electrode 20, a negative electrode 30, and a separator layer 40.

[0025] (positive electrode) The positive electrode 20 includes a positive electrode current collector 21, an intermediate layer 21a, and a positive electrode active material layer 22. The positive electrode current collector 21 can be any conductive material, such as a plate or foil, and can be aluminum, stainless steel, or nickel-plated steel.

[0026] The positive electrode active material layer 22 contains a positive electrode active material. The positive electrode active material layer 22 may further contain a positive electrode binder and a conductive additive.

[0027] The positive electrode active material is not particularly limited, and known positive electrode active materials can be used as appropriate. Examples of positive electrode active materials include lithium cobalt oxide (LCO), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminate, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium iron phosphate, nickel sulfide, copper sulfide, sulfur, iron oxide, vanadium oxide, and the like. These positive electrode active materials may be used individually or in combination of two or more.

[0028] The cathode binder is not particularly limited, and known cathode binders can be used as appropriate. Examples of cathode binders include fluorine-containing resins such as polyvinylidene fluoride, ethylene-containing resins such as styrene-butadiene rubber, ethylene-propylene-diene terpolymer, acrylonitrile-butadiene rubber, fluororubber, polyvinyl acetate, polymethyl methacrylate, polyethylene, polyvinyl alcohol, carboxymethylcellulose or carboxymethylcellulose derivatives (such as salts of carboxymethylcellulose), or nitrocellulose.

[0029] The conductive additive is not particularly limited, and known conductive additives can be used as appropriate. Examples of conductive additives include carbon black such as Ketjenblack and acetylene black, fibrous carbon such as carbon fiber and carbon nanotubes, natural graphite, and artificial graphite.

[0030] (Middle class) The intermediate layer 21a is placed between the positive electrode current collector 21 and the positive electrode active material layer 22. The intermediate layer 21a comprises first particles 21b, which are lithium iron phosphate (LFP) particles, and an insulating material. The insulating material comprises second particles 21c and an intermediate layer binder 21d. The intermediate layer 21a may also contain other materials (e.g., conductive additives used in the positive electrode active material layer 22) in such a way that the sum of the mass percentages of each component does not exceed 100% by mass. Preferably, the intermediate layer 21a is composed of at least the first particles 21b and the insulating material. In this case, the conductive material is the first particles 21b.

[0031] Since the first particle 21b is a lithium iron phosphate particle, it is highly safe and conductive. Specifically, the first particle 21b has the characteristic of being less prone to thermal runaway and less likely to become overheated even when the temperature of the positive electrode 20 rises. Furthermore, because the first particle 21b is conductive, it can maintain the performance of the non-aqueous electrolyte secondary battery 10.

[0032] The second particle 21c is an insulating particle and, as described later, is a thin, plate-shaped particle with a high aspect ratio. The second particle 21c can enhance the safety of the non-aqueous electrolyte secondary battery 10. Specifically, when a sharp foreign object such as a nail pierces the non-aqueous electrolyte secondary battery 10, the second particle 21c is thought to get between the positive electrode current collector 21 and the foreign object, thereby suppressing contact between the foreign object and the positive electrode current collector 21. Therefore, it is thought that a short circuit between the positive electrode 20 and the negative electrode 30 via the foreign object can be suppressed. Furthermore, since the second particle 21c covers the positive electrode current collector 21, it is possible to suppress contact between the positive electrode current collector 21 and the negative electrode 30. However, since the second particle 21c is an insulating particle, it is necessary to appropriately control its content, etc., in order to maintain the performance of the non-aqueous electrolyte secondary battery 10.

[0033] The content of the first particles 21b in the intermediate layer 21a is 70% by mass or more and 90% by mass or less, when the total mass of the intermediate layer 21a is 100% by mass; the content of the second particles 21c in the intermediate layer 21a is 5.0% by mass or more and 20% by mass or less; and the content of the intermediate layer binder 21d in the intermediate layer 21a is 3.0% by mass or more and 10% by mass or less. The content of the first particles 21b is preferably 75% by mass or more and 88% by mass or less, and more preferably 77.5% by mass or more and 87% by mass or less. The content of the second particles 21c is preferably 6.0% by mass or more and 17.5% by mass or less, and more preferably 7.0% by mass or more and 15.0% by mass or less. The content of the intermediate layer binder 21d is preferably 4.0% by mass or more and 9.0% by mass or less, and more preferably 5.0% by mass or more and 8.0% by mass or less. Furthermore, the total content of the first particles 21b and the second particles 21c is 80% by mass or more and 95% by mass or less. Preferably, the total content of the first particles 21b and the second particles 21c is 82% by mass or more and 95% by mass or less, and more preferably 85% by mass or more and 95% by mass or less. By having the intermediate layer 21a contain each component in the above mass percentages, it is possible to maintain the performance of the non-aqueous electrolyte secondary battery 10 while increasing the safety of the non-aqueous electrolyte secondary battery 10.

[0034] The content of the first particle 21b and the second particle 21c in the intermediate layer 21a can be measured, for example, by the following method.

[0035] First, a cross-sectional sample containing the intermediate layer 21a is prepared using a cross-section sample preparation device such as a cross-section polisher. SEM-EDS observation is performed at at least three locations in the prepared cross-sectional sample, including near the center and both ends, to quantify the mass of the major elements contained in the cross-sectional sample. Based on the mass of the identified major elements, the masses of the first particles 21b and the second particles 21c contained in the cross-sectional sample are calculated. Based on the masses of the first particles 21b and the second particles 21c calculated in this way and the mass of the cross-sectional sample, the content of the first particles 21b and the second particles 21c in the intermediate layer 21a can be calculated. The equipment and conditions used for measurement are, for example, as follows. Measurement equipment: Field emission scanning electron microscope JSM-7800F (FE-SEM, manufactured by JEOL Ltd.), energy dispersive analyzer JED100mm (EDS, manufactured by JEOL Ltd.), acceleration voltage: 4kV The particle diameter of the first particle 21b is 0.1 μm or more and 3.0 μm or less. Here, in this embodiment, "particle diameter" means D50, which is 50% of the integrated particle size distribution based on particle size volume in the particle size distribution obtained by the laser diffraction / scattering method. By setting the particle diameter of the first particle 21b to a value within this range, the safety of the non-aqueous electrolyte secondary battery 10 can be enhanced while maintaining the performance of the non-aqueous electrolyte secondary battery 10. Preferably, the particle diameter of the first particle 21b is 0.3 μm or more and 2.0 μm or less, and more preferably 0.5 μm or more and 1.5 μm or less.

[0036] The particle diameter of the second particle 21c is between 2.9 μm and 13.0 μm. Preferably, the particle diameter of the second particle 21c is between 3.5 μm and 12.0 μm, and more preferably between 4.0 μm and 10.0 μm. Furthermore, the aspect ratio (major axis / minor axis) of the second particle 21c, i.e., (D50 determined by laser diffraction / scattering method) / (thickness measured by scanning electron microscope), is between 9.0 and 40.0. Preferably, the aspect ratio of the second particle 21c is between 10.0 and 30.0, and more preferably between 12.0 and 25.0. Here, the major axis of the second particle 21c is the largest diameter of the second particle 21c of interest, and the minor axis is the smallest diameter (i.e., thickness) of the second particle 21c of interest. In this embodiment, the major axis of the second particle 21c is D50 as described above, and the minor axis of the second particle 21c is a value obtained by the following method. That is, after attaching the second particle 21c to the carbon tape, the thickness of any 100 second particles 21c (primary particles) is measured using a scanning electron microscope (e.g., JSM-7800F (manufactured by JEOL Ltd.)). Then, the arithmetic mean of these measurements is taken as the minor axis of the second particle 21c. In this embodiment, since the aspect ratio is within the range described above, it has a thin plate shape. Therefore, the above-described effects are obtained.

[0037] The thickness of the intermediate layer 21a is preferably 0.5 μm or more and 5.0 μm or less. More preferably, the thickness of the intermediate layer 21a is 0.5 μm or more and 4.5 μm or less, and even more preferably 1.0 μm or more and 4.0 μm or less. When the thickness of the intermediate layer 21a is within this range, the safety of the non-aqueous electrolyte secondary battery 10 can be enhanced while maintaining the performance of the non-aqueous electrolyte secondary battery 10. If the thickness of the intermediate layer 21a is less than 0.5 μm, the safety of the non-aqueous electrolyte secondary battery 10 may not be sufficiently enhanced, and if the thickness of the intermediate layer 21a exceeds 5.0 μm, the performance of the non-aqueous electrolyte secondary battery 10 may decrease. In addition, according to this embodiment, since the first particle 21b and the second particle 21c are used in combination, the intermediate layer 21a can be made thinner.

[0038] The thickness of the intermediate layer 21a can be measured, for example, by the following procedure. First, a cross-sectional sample is prepared by cutting the positive electrode 20 along its thickness direction using a cross-sectional sample preparation device such as a cross-polisher. The prepared cross-sectional sample is observed with a scanning electron microscope (SEM), and the thickness of the intermediate layer 21a is calculated from this SEM image. Specifically, the thickness is measured at least three locations in the cross-sectional sample, including near the center and both ends of the intermediate layer 21a, and the average value is taken as the thickness of the intermediate layer 21a.

[0039] The volume resistivity of the first particles 21b under a pressure of 60 MPa is preferably 1.0 Ωcm or more and 5×10 Ωcm or less. The volume resistivity of the first particles 21b under a pressure of 60 MPa is more preferably 1.0 Ωcm or more and 30 Ωcm or less, and still more preferably 1.0 Ωcm or more and 20 Ωcm or less. In this case, the effects of the present embodiment can be obtained more effectively. More specifically, if lithium iron phosphate having a high volume resistivity is used as the first particles 21b, it is necessary to add a conductive auxiliary agent such as carbon black or carbon nanotube and an additional polymer as a dispersant thereof in order to ensure the conductivity of the intermediate layer 21a, which may reduce the content of the first and second particles 21b, 21c having a high safety enhancement effect. As a result, the performance or safety of the non-aqueous electrolyte secondary battery 10 may be degraded. Examples of the method for setting the volume resistivity of the first particles 21b to a value within this range include a method of coating the first particles 21b with a suitable conductive material (carbon or the like). As a method of coating the first particles 21b with a conductive material, for example, 5% by mass of coal tar pitch is added to and mixed with the first particles 21b, and the mixture is fired at 600°C for 1 hour in a firing furnace under a nitrogen atmosphere.

[0040] The specific surface area (BET) of the first particles 21b calculated from an adsorption isotherm measured by causing nitrogen to adsorb to the first particles 21b is preferably 1.0 m 2 / g or more and 20 m 2 / g or less. The specific surface area (BET) of the first particles 21b is more preferably 1.0 m 2 / g or more and 18 m 2 / g or less, and still more preferably 1.0 m 2 / g or more and 15 m 2 / g or less. The specific surface area (BET) of the second particles 21c calculated from an adsorption isotherm measured by causing nitrogen to adsorb to the second particles 21c is preferably 0.5 m 2 / g or more and 50 m 2 / g or less. The specific surface area (BET) of the second particles 21c is more preferably 0.5 m 2 / g or more and 40 m 2 / g or less, and still more preferably 0.5 m2 / g or more 30m 2 The value is less than or equal to / g. The effects of this embodiment are more effectively obtained when the specific surface area of ​​each particle falls within these ranges.

[0041] The second particle 21c is preferably one or more selected from the group consisting of boehmite, mica, and boron nitride. Alternatively, the second particle 21c may include composite particles in which the surface and interior of metal hydroxide particles are modified with a flame retardant, and the metal hydroxide may be one or more selected from the group consisting of aluminum hydroxide, pseudoboehmite, and boehmite. In this case, the flame retardant is preferably one or more selected from the group consisting of phosphoric acid, phosphate esters, phosphonic acid, and phosphinic acid. In other words, the second particle 21c may consist of one type of these particles, or it may consist of two or more types. The effects of this embodiment are more effectively obtained when the second particle 21c is one or more selected from these particles.

[0042] Here, if the second particle 21c contains the composite particle described above, it is preferable that, when the total mass of the composite particle is 100% by mass, the aluminum element content measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES) is 5% by mass or more and 30% by mass or less, and the phosphorus element content is 5% by mass or more and 30% by mass or less. The aluminum element content is more preferably 5% by mass or more and 25% by mass or less, and even more preferably 5% by mass or more and 20% by mass or less. The phosphorus element content is more preferably 8% by mass or more and 25% by mass or less, and even more preferably 10% by mass or more and 20% by mass or less. In this case, the effects of this embodiment can be obtained more effectively.

[0043] The method for producing the composite particles is not particularly limited, but for example, composite particles can be produced by heating an aqueous dispersion of metal hydroxide particles and a flame retardant.

[0044] The intermediate layer binder 21d is not particularly limited as long as the effects of this embodiment can be obtained, but it is preferable to include a copolymer containing units derived from (meth)acrylonitrile monomers and units derived from (meth)acrylic acid monomers. Here, in the copolymer, when the total mass of the copolymer is 100% by mass, it is preferable that the units derived from (meth)acrylonitrile monomers are 90% by mass or more and 99% by mass or less, and the units derived from (meth)acrylic acid monomers are 1% by mass or more and 10% by mass or less. The units derived from (meth)acrylonitrile monomers are more preferably 92% by mass or more and 98% by mass or less, and even more preferably 94% by mass or more and 97% by mass or less. The units derived from (meth)acrylic acid monomers are more preferably 1% by mass or more and 8% by mass or less, and even more preferably 1% by mass or more and 5% by mass or less. In this case, the effects of this embodiment can be obtained more effectively.

[0045] Units derived from (meth)acrylonitrile monomers include, for example, acrylonitrile and methacrylonitrile.

[0046] Units derived from (meth)acrylic acid monomers include, for example, acrylic acid, methacrylic acid, and methyl methacrylate.

[0047] The method for polymerizing the (meth)acrylonitrile monomer and the (meth)acrylic acid monomer is not particularly limited. For example, an aqueous solution of an initiator may be added to an aqueous dispersion of both monomers and heated.

[0048] Since the non-aqueous electrolyte secondary battery 10 according to this embodiment has the above-described intermediate layer 21a, it is possible to enhance the safety of the non-aqueous electrolyte secondary battery 10 while maintaining its performance.

[0049] (Negative electrode) The negative electrode 30 includes a negative electrode current collector 31 and a negative electrode active material layer 32. The negative electrode current collector 31 can be any conductive material, for example, a plate or foil, and can be made of copper, stainless steel, nickel-plated steel, etc. The negative electrode active material layer 32 is not particularly limited, and any known negative electrode active material layer 32 can be used as appropriate. The negative electrode active material layer 32 includes, for example, a negative electrode active material and a negative electrode binder. The negative electrode active material layer 32 may further contain a conductive additive. Any known negative electrode active material can be used as appropriate. Examples of negative electrode active materials include graphite active materials (artificial graphite, natural graphite, a mixture of artificial graphite and natural graphite, natural graphite coated with artificial graphite, etc.), a mixture of fine particles of silicon (Si) or tin (Sn) or their oxides and graphite active material, fine particles of silicon or tin, an alloy based on silicon or tin, and Li4Ti5O 12 Titanium oxide (TiOx)-based compounds such as those mentioned above can be used.

[0050] The negative electrode binder is not particularly limited, as long as it can bind the negative electrode active material and conductive additive onto the negative electrode current collector 31. Examples of negative electrode binders include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), styrene-butadiene copolymer (SBR), and metal salts of carboxymethylcellulose (CMC).

[0051] As a conductive additive, the same one used in the positive electrode 20 can be used.

[0052] (Separator layer) The separator layer 40 includes a separator and a non-aqueous electrolyte. Known separators and non-aqueous electrolytes can be used as appropriate. Preferably, the separator is a porous membrane or nonwoven fabric that exhibits excellent high-rate discharge performance, either alone or in combination. Examples of materials that make up the separator include polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-perfluorovinyl ether copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-fluoroethylene copolymer, vinylidene fluoride-hexafluoroacetone copolymer, vinylidene fluoride-ethylene copolymer, vinylidene fluoride-propylene copolymer, vinylidene fluoride-trifluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, and vinylidene fluoride-ethylene-tetrafluoroethylene copolymer.

[0053] A non-aqueous electrolyte has a composition in which an electrolyte salt is contained in a non-aqueous solvent, which is the solvent for the electrolyte. Examples of non-aqueous solvents include cyclic carbonate esters such as propylene carbonate, ethylene carbonate, butylene carbonate, chloroethylene carbonate, fluoroethylene carbonate, and vinylene carbonate; cyclic esters such as γ-butyrolactone and γ-valerolactone; linear carbonates such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; linear esters such as methyl formate, methyl acetate, methyl butyrate, ethyl propionate, and propyl propionate; tetrahydrofuran or its derivatives; ethers such as 1,3-dioxane, 1,4-dioxane, 1,2-dimethoxyethane, 1,4-dibutoxyethane, or methyl diglyme, ethylene glycol monopropyl ether, and propylene glycol monopropyl ether; nitriles such as acetonitrile and benzonitrile; dioxolane or its derivatives; ethylene sulfide, sulfolane, and sultone.

[0054] Examples of electrolyte salts include LiClO4, LiBF4, LiAsF6, LiPF6, and LiPF6-x(C). n F 2n+1 )x[However, 1 <x<6、n=1or2]、LiSCN、LiBr、LiI、Li2SO4、Li2B 10 Cl 10 Inorganic ionic salts containing lithium (Li), sodium (Na), or potassium (K), such as NaClO4, NaI, NaSCN, NaBr, KClO4, KSCN, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiC(C2F5SO2)3, (CH3)4NBF4, (CH3)4N Examples include organic ionic salts such as Br, (C2H5)4NClO4, (C2H5)4NI, (C3H7)4NBr, (n-C4H9)4NClO4, (n-C4H9)4NI, (C2H5)4N-maleate, (C2H5)4N-benzoate, (C2H5)4N-phtalate, lithium stearylsulfonate, lithium octylsulfonate, and lithium dodecylbenzenesulfonate.

[0055] The non-aqueous electrolyte secondary battery 10 has a desired shape (for example, cylindrical, rectangular, laminated, button-shaped, etc.).

[0056] Since the non-aqueous electrolyte secondary battery 10 according to this embodiment includes the intermediate layer 21a with the above-described configuration, it is possible to enhance the safety of the non-aqueous electrolyte secondary battery 10 while maintaining its performance.

[0057] <Manufacturing method for non-aqueous electrolyte secondary batteries> Next, a method for manufacturing the non-aqueous electrolyte secondary battery 10 according to this embodiment will be described. It should be noted that the manufacturing method described below is merely an example, and the non-aqueous electrolyte secondary battery 10 may be manufactured by other methods.

[0058] (Preparation of the intermediate layer) First, the intermediate layer slurry is prepared. Specifically, the intermediate layer slurry is prepared by dispersing a mixture of the first particles 21b and an insulating material in the above-mentioned proportions in a suitable solvent. Next, the intermediate layer slurry is coated onto the positive electrode current collector 21 and dried. This forms an intermediate layer 21a on the positive electrode current collector 21. Possible coating methods include the knife coater method, gravure coater method, reverse roll coater method, and slit die coater method.

[0059] (Fabrication of the positive electrode active material layer) First, the positive electrode mixture slurry is prepared. Specifically, the positive electrode mixture slurry is prepared by dispersing a mixture of the above-mentioned positive electrode active material, preferably further mixed with a positive electrode binder and a conductive additive in a desired proportion, in a suitable solvent. Next, the positive electrode mixture slurry is coated onto the intermediate layer 21a and dried. This forms a positive electrode active material layer 22 on the intermediate layer 21a. Through these steps, a positive electrode 20 is manufactured, which includes an intermediate layer 21a positioned between the positive electrode current collector 21 and the positive electrode active material layer 22.

[0060] (Fabrication of the negative electrode) First, the negative electrode mixture slurry is prepared. Specifically, the negative electrode mixture slurry is prepared by dispersing a mixture of negative electrode active material and negative electrode binder in a suitable solvent in a desired ratio. Next, the negative electrode mixture slurry is coated onto the negative electrode current collector 31 and dried. This forms a negative electrode active material layer 32 on the negative electrode current collector 31.

[0061] (Fabrication of non-aqueous electrolyte secondary batteries) An electrode structure is fabricated by placing a positive electrode 20 and a negative electrode 30 opposite each other via a separator and compressing them. Next, the electrode structure is processed into a desired shape (e.g., cylindrical, rectangular, laminated, button-shaped, etc.). Next, the electrode structure is placed in a desired battery container. Finally, an electrolyte is injected into the battery container, and the battery container is sealed under reduced pressure. This completes the fabrication of a non-aqueous electrolyte secondary battery 10. [Examples]

[0062] The present invention will be described in more detail below based on specific examples. However, the following examples are merely examples of the present invention, and the present invention is not limited to these examples.

[0063] <Preparation of copolymers> The following copolymers A and B were prepared as intermediate layer binders, which are insulating materials included in the intermediate layer.

[0064] (Copolymer A) In a 2000 ml separable flask equipped with a mechanical stirrer, stirring rod, and thermometer, 97.0 g of acrylonitrile, 3.0 g of acrylic acid, and 846.2 g of deionized water were charged and stirred at 400 rpm. Next, the system was purged with nitrogen, and the temperature was raised with the jacket temperature set to 85°C. When the system temperature reached 60°C, an initiator aqueous solution of 4.2 g of ammonium peroxodisulfate dissolved in 50.0 g of deionized water was added to the separable flask. With the jacket temperature set to 85°C, stirring was continued for 6 hours from the addition of the initiator to obtain a yellow polymer suspension. The suspension after the reaction was filtered and washed with deionized water and methanol to remove unreacted monomers, and the solid on the filter paper was vacuum dried to obtain copolymer A.

[0065] (Copolymer B) In a 2000 ml separable flask equipped with a mechanical stirrer, stirring rod, and thermometer, 91.0 g of acrylonitrile, 9.0 g of acrylic acid, and 846.2 g of deionized water were charged and stirred at 400 rpm. Next, the system was purged with nitrogen, and the temperature was raised with the jacket temperature set to 85°C. When the system temperature reached 60°C, an initiator aqueous solution of 4.2 g of ammonium peroxodisulfate dissolved in 50.0 g of deionized water was added to the separable flask. With the jacket temperature set to 85°C, stirring was continued for 6 hours from the addition of the initiator to obtain a yellow polymer suspension. The suspension after the reaction was filtered and washed with deionized water and methanol to remove unreacted monomers, and the solid on the filter paper was vacuum dried to obtain copolymer B.

[0066] <Production of composite particles> As the second particle, which is an insulating material contained in the intermediate layer, the following composite particles A and B were fabricated.

[0067] (Composite particle A) Boehmite (D50: 0.45 μm, BET: 22.5 μm) 2 1.0 g of (1 / g) and 5.0 g of methylphosphinic acid were dispersed in 50 cc of a mixed solution of ethanol and purified water (mixing volume ratio 1:1), and the mixture was heated at 70°C for 24 hours. The resulting product was then filtered with water and ethanol, and the solid on the filter paper was vacuum-dried to obtain composite particle A.

[0068] (Composite particle B) Pseudoboehmite (D50: 1.8 μm, BET: 318 μm) 2 Composite particle B was obtained by performing the same procedure as for composite particle A, except that 1.0 g of (1 g) and 5.0 g of phenylphosphonic acid were dispersed in 50 cc of a mixed solution of ethanol and purified water (mixing volume ratio 1:1).

[0069] <Intermediate layer fabrication> The intermediate layers for each example and comparative example were prepared using the following method.

[0070] (Example 1) An intermediate layer slurry was prepared by dispersing lithium iron phosphate (as shown in Table 1-1), boron nitride (as shown in Table 1-2), and polyvinylidene fluoride (PVDF) in N-methyl-2-pyrrolidone solvent in a solid content mass ratio of 84:10:6. Subsequently, the coating amount (surface density) of the mixture after drying was 0.225 mg / cm² per side. 2 An intermediate layer was prepared by coating and drying an intermediate layer mixture slurry on one or both sides of an aluminum current collector foil. The thickness of the intermediate layer was 1.0 μm.

[0071] (Example 2) An intermediate layer slurry was prepared by dispersing lithium iron phosphate A (with the properties shown in Table 1-1), boron nitride B (with the properties shown in Table 1-2), copolymer A, and polyacrylic acid (PAA) in an N-methyl-2-pyrrolidone solvent in a solid content mass ratio of 81:10:6:3. Subsequently, the amount of the mixture applied (surface density) after drying was 0.7 mg / cm² per side. 2 An intermediate layer was prepared by coating and drying the slurry on one or both sides of the aluminum current collector foil. The thickness of the intermediate layer was 3.0 μm.

[0072] (Example 3) An intermediate layer was prepared using the same procedure as in Example 2, except that lithium iron phosphate B with the properties shown in Table 1-1, boehmite A with the properties shown in Table 1-2, copolymer A, and polyacrylic acid were dispersed and mixed in an N-methyl-2-pyrrolidone solvent in a solids mass ratio of 75:15:7:3. The thickness of the intermediate layer was 3.0 μm.

[0073] (Example 4) An intermediate layer was prepared using the same procedure as in Example 2, except that lithium iron phosphate A with the properties shown in Table 1-1, composite particles A with the properties shown in Table 1-2, copolymer A, and polyacrylic acid were dispersed and mixed in an N-methyl-2-pyrrolidone solvent in a solid content mass ratio of 90:5:3.5:1.5. The thickness of the intermediate layer was 3.0 μm.

[0074] (Example 5) An intermediate layer was prepared using the same procedure as in Example 2, except that lithium iron phosphate A with the properties shown in Table 1-1, composite particles B with the properties shown in Table 1-2, copolymer B, and polyvinylidene fluoride were dispersed and mixed in an N-methyl-2-pyrrolidone solvent in a solid content mass ratio of 87:5:5.5:2.5. The thickness of the intermediate layer was 3.0 μm.

[0075] (Example 6) An intermediate layer was prepared using the same procedure as in Example 2, except that lithium iron phosphate B with the properties shown in Table 1-1, boron nitride C with the properties shown in Table 1-2, copolymer B, and polyacrylic acid were dispersed and mixed in an N-methyl-2-pyrrolidone solvent in a solids mass ratio of 70:20:7:3. The thickness of the intermediate layer was 2.0 μm.

[0076] (Example 7) An intermediate layer slurry was prepared by dispersing lithium iron phosphate B (with the properties shown in Table 1-1), boron nitride A (with the properties shown in Table 1-2), copolymer A, and polyacrylic acid in an N-methyl-2-pyrrolidone solvent in a solid content mass ratio of 81:10:6:3. Subsequently, the amount of the mixture applied (surface density) after drying was 1.0 mg / cm² on one side. 2 An intermediate layer was prepared by coating and drying the slurry on one or both sides of the aluminum current collector foil. The thickness of the intermediate layer was 4.5 μm. (Example 8) An intermediate layer slurry was prepared by dispersing lithium iron phosphate (as shown in Table 1-1), boron nitride (as shown in Table 1-2), copolymer A, and polyacrylic acid in N-methyl-2-pyrrolidone solvent in a solid content mass ratio of 81:10:6:3. Then, the slurry was applied to one side at a surface density of 0.7 mg / cm². 2 An intermediate layer was prepared by coating and drying the slurry on one or both sides of the aluminum current collector foil. The thickness of the intermediate layer was 3.0 μm.

[0077] (Comparative Example 2) An intermediate layer slurry was prepared by dispersing lithium iron phosphate A and polyvinylidene fluoride, with the physical properties shown in Table 1-1, in N-methyl-2-pyrrolidone solvent at a solid content mass ratio of 91:9. Subsequently, the amount of the mixture applied (surface density) after drying was 1.0 mg / cm² on one side. 2 An intermediate layer was prepared by coating and drying the slurry on one or both sides of the aluminum current collector foil. The thickness of the intermediate layer was 4.0 μm.

[0078] (Comparative Example 3) An intermediate layer slurry was prepared by dispersing lithium iron phosphate A and polyvinylidene fluoride, with the physical properties shown in Table 1-1, in an N-methyl-2-pyrrolidone solvent at a solid content mass ratio of 91:9. Subsequently, the amount of the mixture applied (surface density) after drying was 0.5 mg / cm² per side. 2 An intermediate layer was prepared by coating and drying the slurry on one or both sides of the aluminum current collector foil. The thickness of the intermediate layer was 2.0 μm.

[0079] (Comparative Example 4) An intermediate layer slurry was prepared by dispersing lithium iron phosphate A and polyvinylidene fluoride, with the physical properties shown in Table 1-1, in an N-methyl-2-pyrrolidone solvent at a solid content mass ratio of 91:9. Subsequently, the coating amount (surface density) of the mixture after drying was 2.0 mg / cm² on one side. 2 An intermediate layer was prepared by coating and drying the slurry on one or both sides of the aluminum current collector foil. The thickness of the intermediate layer was 8.0 μm.

[0080] (Comparative Examples 5-9) An intermediate layer slurry was prepared by dispersing lithium iron phosphate A or B with the properties shown in Table 1-1, a second particle with the properties shown in Table 1-2, and polyvinylidene fluoride in an N-methyl-2-pyrrolidone solvent in a solid content mass ratio of 81:10:9. Subsequently, the amount of the mixture applied (surface density) after drying was 0.9 mg / cm² on one side. 2 An intermediate layer was prepared by coating and drying the slurry on one or both sides of the aluminum current collector foil. The thickness of the intermediate layer was 4.0 μm.

[0081] (Comparative Example 10) An intermediate layer slurry was prepared by dispersing alumina with the properties shown in Table 1-1, boron nitride A with the properties shown in Table 1-2, and polyvinylidene fluoride in an N-methyl-2-pyrrolidone solvent in a solid content mass ratio of 81:10:9. Subsequently, the amount of the mixture applied (surface density) after drying was 0.8 mg / cm² on one side. 2An intermediate layer was prepared by coating and drying the slurry on one or both sides of the aluminum current collector foil. The thickness of the intermediate layer was 4.0 μm. (Comparative Example 11) An intermediate layer slurry was prepared by dispersing lithium iron phosphate A with the properties shown in Table 1-1, boron nitride A with the properties shown in Table 1-2, copolymer A, and polyacrylic acid in N-methyl-2-pyrrolidone solvent in a solid content mass ratio of 60:30:6:4. Then, the amount of the mixture applied (surface density) was 1.0 mg / cm² on one side. 2 An intermediate layer was prepared by coating and drying the slurry on one or both sides of the aluminum current collector foil. The thickness of the intermediate layer was 4.5 μm. (Comparative Example 12) An intermediate layer slurry was prepared by dispersing lithium iron phosphate (with the properties shown in Table 1-1), boron nitride (with the properties shown in Table 1-2), and polyvinylidene fluoride in an N-methyl-2-pyrrolidone solvent in a solid content mass ratio of 81:10:9. Then, the slurry was prepared with a slurry coating amount (surface density) of 1.1 mg / cm² on one side. 2 An intermediate layer was prepared by coating and drying the slurry on one or both sides of the aluminum current collector foil. The thickness of the intermediate layer was 5.0 μm. (Comparative Example 13) An intermediate layer slurry was prepared by dispersing lithium iron phosphate A (with the properties shown in Table 1-1), boron nitride E (with the properties shown in Table 1-2), copolymer A, and polyacrylic acid in an N-methyl-2-pyrrolidone solvent in a solid content mass ratio of 81:10:6:3. Then, the slurry was applied to one side with a coating amount (surface density) of 1.0 mg / cm². 2 An intermediate layer was prepared by coating and drying the slurry on one or both sides of the aluminum current collector foil. The thickness of the intermediate layer was 4.5 μm.

[0082] <Cathode fabrication> The positive electrodes for each example and comparative example were prepared using the following method.

[0083] (Examples 1-8, Comparative Examples 2-13) A cathode mixture slurry was prepared by dispersing LiCoO2 (D50: 17 μm), acetylene black, and polyvinylidene polyfluoride in an N-methyl-2-pyrrolidone solvent with a solid content mass ratio of 97.7:1.0:1.3 and mixing them. Subsequently, the amount of mixture coated (surface density) after drying was 20.50 mg / cm² on one side. 2 The cathode was fabricated by coating the cathode mixture slurry onto an intermediate layer and drying it, then pressing it with a roll press machine until the cathode active material layer density was 4.15 g / cc.

[0084] (Comparative Example 1) The positive electrode was prepared using the same procedure as in Example 1, except that the positive electrode mixture slurry described above was coated onto one or both sides of the aluminum current collector foil and dried.

[0085] <Negative electrode fabrication> (Examples 1-8, Comparative Examples 1-13) A negative electrode mixture slurry was prepared by dissolving and dispersing synthetic graphite, carboxymethylcellulose sodium salt (CMC), and styrene-butadiene aqueous dispersions in an aqueous solvent in a mass ratio of 97.5:1.0:1.5 for each component as dry powder (solid content) without solvent. Subsequently, the coating amount (surface density) of the mixture after drying was 15.0 mg / cm². 2 The negative electrode mixture slurry was coated onto one or both sides of the copper foil, which is the main negative electrode element, and then dried. After that, the negative electrode was manufactured by pressing it with a roll press machine to achieve a negative electrode active material layer density of 1.65 g / cc.

[0086] <Fabrication of non-aqueous electrolyte secondary batteries> (Examples 1-8, Comparative Examples 1-13) An electrode stack was fabricated by stacking multiple positive and negative electrodes via a porous polypropylene separator to achieve a battery design capacity of 300 mAh. For the positive and negative electrodes placed inside the electrode stack, active material layers were formed on both sides of the current collector, while for the positive or negative electrode placed in the outermost layer, an active material layer was formed on only one side. Specifically, the electrode plate area was 8.5 cm². 2 The positive electrode (5 plates on both sides) has a plate area of ​​10.0 cm².2 Negative electrodes (four on both sides and two on one side) were fabricated. Next, nickel and aluminum lead wires were welded to the negative electrode current collector and positive electrode current collector of the electrode stack described above, respectively. Then, the electrode stack was housed in an aluminum laminate film with the lead wires exposed. Next, an electrolyte solution was poured into the aluminum laminate film and sealed under reduced pressure to fabricate a pre-charge secondary battery cell (non-aqueous electrolyte secondary battery). The electrolyte solution used was a solvent mixture of ethylene carbonate / dimethyl carbonate / fluoroethylene carbonate in a volume ratio of 15 / 80 / 5, in which 1.3 M LiPF6 and 1 mass% vinylene carbonate were dissolved.

[0087] <Evaluation of the first and second particles> The first and second particles used in the examples and comparative examples were evaluated by the following method.

[0088] (Particle diameters of the first and second particles) As described above, the particle sizes of the first and second particles were defined as 50% (D50) of the integrated particle size distribution based on particle size volume in the particle size distribution obtained by laser diffraction / scattering. The measurement equipment and measurement conditions are as follows.

[0089] Measurement device: Laser diffraction / scattering particle size distribution analyzer MasterSizer 3000 (manufactured by Malvern Panalytic Corporation) Transparency: Transparent Shape: non-spherical Measurement time: 3 seconds Laser scattering intensity: 4.0 Number of repetitions: 3 Refractive index: a. Ethanol solvent: 1.36 b. Lithium iron phosphate: 2.42 c. Boron nitride: 1.74 d. Boehmite and composite particles: 1.65 e. Alumina: 1.76

[0090] (Volume resistivity at 60 MPa pressure) Using the MCP-PD51 manufactured by Nitto Seiko Analytech Co., Ltd., the first particles filled into a cylindrical cylinder were pressure-molded using a hydraulic press, and the volume resistivity of the powder was measured. The measurement conditions were as follows.

[0091] Load: 18.85kN Electrode spacing: 3.0 mm Electrode radius: 0.7mm Sample radius: 10.0 mm Probe used: 4-point probe (Specific surface area of ​​the first and second particles) The specific surface area (BET, which is the specific surface area calculated based on the adsorption isotherm measured by adsorbing nitrogen gas, as described above) of the first and second particles was measured in accordance with JIS K6217-2 using a gas adsorption amount measuring device (BELSORP, manufactured by Microtrac-Bel).

[0092] (The aspect ratio of the second particle: (D50 determined by laser diffraction / scattering) / (thickness measured by scanning electron microscopy)) The particle diameter (D50) obtained by the laser diffraction / scattering method described above was used as the major axis of the second particle.

[0093] The minor axis of the second particle was measured by the following method. After attaching the second particle to a carbon tape, the thickness of 100 arbitrary primary particles was measured using a scanning electron microscope JSM-7800F (manufactured by JEOL Ltd.). The arithmetic mean of these measurements was then taken as the minor axis of the second particle. Next, the aspect ratio was calculated as (D50 obtained by laser diffraction / scattering) / (thickness measured by scanning electron microscope).

[0094] (Elemental analysis of the second particle) Using an inductively coupled plasma emission spectrometer (ICP-AES, Agilent Technologies, model 5110 VDV), the Al and P elements contained in the second particle of each example and comparative example were quantitatively analyzed in accordance with JIS K0116:2014.

[0095] <Evaluation of non-aqueous electrolyte secondary batteries> (Calculation of cell ratio capacity) The secondary battery cells prepared in Examples 1-8 and Comparative Examples 1-13 were charged with a constant current at 0.1C to 4.4V in a constant temperature bath at 25°C, followed by constant voltage charging at 4.4V to 0.05C. Then, they were discharged with a constant current at 0.1C to 2.75V. Furthermore, in a constant temperature bath at 25°C, one cycle of constant current charging at 0.2C, constant voltage charging at 0.05C, and constant current discharge at 0.2C was performed under conditions of a charging termination voltage of 4.4V and a discharge termination voltage of 3.0V, and the initial discharge capacity was measured. The cell specific capacity (mAh / g) was calculated by dividing this initial discharge capacity by the total weight of the positive electrode active material layer including the intermediate layer (positive electrode plate weight - current collector foil weight).

[0096] (Evaluation of cell resistance (Ω)) The cell resistance of the initial secondary battery cells, whose cell ratio capacity had been calculated, was measured at 25°C using the AC impedance (EIS) method. This was done by constant current charging at 0.2C and constant voltage charging at 0.05C under the condition of a charging termination voltage of 4.4V. The measurement conditions were a frequency range of 100kHz to 100mHz and an applied voltage of 10mV. A VMP-3Potentiostat manufactured by BioLogic was used as the measurement device for this EIS method. The size of the semicircular arc in the Nyquist plot obtained from the measurement results was defined as the cell resistance.

[0097] (Cycle characteristics) Secondary battery cells, whose cell ratio capacity was calculated, underwent a 100-cycle life test at 45°C, with a charge termination voltage of 4.4V and a discharge termination voltage of 3.0V. The test involved constant current charging at 0.5C, constant voltage charging at 0.05C, and constant current discharge at 0.5C. After 100 cycles, the discharge capacity was measured at constant current charging of 0.2C, constant voltage charging of 0.05C, and discharge at 0.2C. The capacity retention rate after 100 cycles was determined by dividing the measured capacity by the initial discharge capacity.

[0098] (Nail-piercing test) A nail-piercing test was performed on the center of the pre-charged secondary battery cells prepared in Examples 1-8 and Comparative Examples 1-13 by driving a 3mm diameter nail at a speed of 1mm / s. An "abnormality" was defined as the external battery temperature exceeding 50°C 5 seconds after nail penetration. The same nail-piercing test was performed on 10 pre-charged secondary battery cells, and the abnormality rate was evaluated.

[0099] <Evaluation Results> Tables 1-1 and 1-2 show the physical properties (types, properties, and locations of the first and second particles, etc.) of Examples 1-8 and Comparative Examples 1-13 described above. In Table 1-2, "AA" represents acrylic acid, "AN" represents acrylonitrile, "PAA" represents polyacrylic acid, and "PVDF" represents polyvinylidene fluoride. Furthermore, Table 2 shows the evaluation results for Examples 1-8 and Comparative Examples 1-13.

[0100] [Table 1-1]

[0101] [Table 1-2]

[0102] [Table 2]

[0103] As shown in the results in Table 2, in Examples 1 to 8, the rate of abnormal occurrences in the nail-insertion test was kept sufficiently low compared to Comparative Example 1, which does not have an intermediate layer, Comparative Example 10, which does not contain lithium iron phosphate as the first particle in the intermediate layer, Comparative Examples 2 to 3, which do not contain the second particle in the intermediate layer, and Comparative Examples 5 to 9, in which the aspect ratio of the second particle in the intermediate layer is less than 9.0. In other words, in Examples 1 to 8, even if a short circuit in the battery is more likely to occur due to nail penetration, the rate of abnormal occurrences caused by the rise in temperature inside the battery was kept sufficiently low. This effect is thought to be because when a nail penetrates the intermediate layer containing the second particle with a high aspect ratio, the second particle with a high aspect ratio deforms, thereby reducing the exposure rate of the current collector foil.

[0104] In addition, in Examples 4 and 5, where composite particles modified on the surface and inside with phosphoric acid, a flame retardant, are used as the second particle, it is considered that the heat generated at the short-circuit location can be reduced by the aforementioned flame retardant, even when a minute short circuit occurs.

[0105] Furthermore, in Comparative Example 4, when the thickness of the intermediate layer was increased without including the second particle in the intermediate layer, the rate of abnormal occurrence was reduced, but there was a significant decrease in cell specific capacity, an increase in cell resistance, and a deterioration in cycle life characteristics. In contrast, in Examples 1 to 8, which included the second particle with an adjusted aspect ratio in the intermediate layer, the above-mentioned deterioration in battery performance was suppressed, and it is considered that both enhanced cell safety and cell characteristics were achieved. Comparative Example 11 did not satisfy the requirements of this embodiment in terms of the content of the first and second particles, Comparative Example 12 had a particle diameter of the first particle exceeding 3.0 μm, and Comparative Example 13 had a particle diameter of the second particle exceeding 13.0 μm. Comparative Example 11 showed a significant decrease in cell specific capacity, an increase in cell resistance, and a deterioration in cycle life characteristics. Comparative Example 12 showed a significant decrease in cell specific capacity, an increase in cell resistance, and a deterioration in cycle life characteristics, in addition to a high rate of abnormal occurrences in the nail-insertion test. Comparative Example 13 also showed a significant decrease in cell specific capacity, an increase in cell resistance, and a deterioration in cycle life characteristics.

[0106] Based on the experimental results described above, according to the present invention, by setting the particle size of lithium iron phosphate, which is the first particle constituting the intermediate layer, to a value within an appropriate range, setting the particle size and aspect ratio of the second particle to a value within an appropriate range, and in addition, appropriately adjusting the composition of the intermediate layer, it is possible to suppress internal short circuits that occur when a nail is driven into a non-aqueous electrolyte secondary battery, and to suppress the deterioration of battery performance such as specific capacity and cycle characteristics while sufficiently suppressing the rise in internal temperature.

[0107] <Expansion of the Embodiment> Although the present inventors have described the invention in detail based on embodiments, it goes without saying that the present invention is not limited thereto and can be modified in various ways without departing from its essence. [Explanation of Symbols]

[0108] 10 Non-aqueous electrolyte secondary battery, 20 Positive electrode, 21 Positive electrode current collector, 21a Intermediate layer, 22 Positive electrode active material layer, 30 Negative electrode, 31 Negative electrode current collector, 32 Negative electrode active material layer, 40 Separator layer

Claims

1. Positive electrode current collector and The positive electrode active material layer, A positive electrode for a non-aqueous electrolyte secondary battery, comprising at least an intermediate layer disposed between the positive electrode current collector and the positive electrode active material layer, The intermediate layer comprises first particles, which are lithium iron phosphate particles, and an insulating material. The insulating material comprises a second particle and a binder. When the total mass of the intermediate layer is 100% by mass, the content of the first particles in the intermediate layer is 70% by mass or more and 90% by mass or less, the content of the second particles in the intermediate layer is 5.0% by mass or more and 20% by mass or less, and the content of the binder in the intermediate layer is 3.0% by mass or more and 10% by mass or less. The total content of the first particles and the second particles is 80% by mass or more and 95% by mass or less. The particle diameter of the first particle is 0.1 μm or more and 3.0 μm or less. A positive electrode for a non-aqueous electrolyte secondary battery, wherein the particle diameter of the second particle is 2.9 μm or more and 13.0 μm or less, and the (D50 determined by laser diffraction / scattering method) / (thickness measured by scanning electron microscope) of the second particle is 9.0 or more and 40.0 or less.

2. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the thickness of the intermediate layer is 0.5 μm or more and 5.0 μm or less.

3. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the volume resistivity of the first particle when pressurized at 60 MPa is 1.0 Ωcm or more and 5 × 10 Ωcm or less.

4. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the intermediate layer is composed of at least the first particles and the insulating material.

5. The binder comprises a copolymer containing units derived from a (meth)acrylonitrile monomer and units derived from a (meth)acrylic acid monomer, wherein in the copolymer, when the total mass of the copolymer is 100% by mass, the units derived from the (meth)acrylonitrile monomer are 90% by mass or more and 99% by mass or less, and the units derived from the (meth)acrylic acid monomer are 1% by mass or more and 10% by mass or less, as described in claim 1.

6. The specific surface area (BET) of the first particle, calculated by measuring the adsorption isotherm after adsorbing nitrogen onto the first particle, is 1.0 m². 2 / g or more 20m 2 / g or less, The specific surface area (BET) of the second particle, calculated by the adsorption isotherm obtained by adsorbing nitrogen onto the second particle, is 0.5 m². 2 / g or more 50m 2 A positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the value is less than or equal to / g.

7. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the second particle is one or more selected from the group consisting of boehmite, mica, and boron nitride.

8. The second particle comprises composite particles in which the surface and interior of metal hydroxide particles are modified with a flame retardant. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the metal hydroxide is one or more selected from the group consisting of aluminum hydroxide, pseudoboehmite, and boehmite.

9. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 8, wherein the flame retardant comprises one or more selected from the group consisting of phosphoric acid, phosphate esters, phosphonic acid, and phosphinic acid.

10. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 9, wherein, when the total mass of the composite particles is 100% by mass, the content of aluminum element measured by inductively coupled plasma atomic emission spectrometer (ICP-AES) is 5% by mass or more and 30% by mass or less, and the content of phosphorus element is 5% by mass or more and 30% by mass or less.

11. A non-aqueous electrolyte secondary battery comprising a positive electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Positive electrode for lithium secondary battery and lithium secondary battery

    JP2023517214A